Eficácia de procedimentos para maximizar senso de bem-estar e competência parental a mulheres vitimizadas - Santini, Paolla Magioni (Universidade Federal de São Carlos, 2011)
Studies have shown that inappropriate parenting styles are developed by learning parental behaviors modeled by their own parents. Furthermore, parents with a history of childhood aggression tend to continue struggling with social, behavioral and health problems, as well as their children. Thus, interventions are necessary so that parents can learn positive ways to set limits, preventing child behavior problems. The Projeto Parceria (Project Partnership) is a Brazilian parenting program which mixes Psychotherapeutic (Unit 1) and Educational (Unit 2) components to mothers with a history of domestic violence to prevent behavior problems in children. The objective of this study was to compare the efficacy of three different intervention procedures in terms of mothers well-being and sense of parental competence: a) Unit 1 followed by Unit 2, b) Unit 2 followed by Unit 1, and c) Unit 1 and 2 done simultaneously. Nine mothers with history of violence participated of the study and their 4-12 year old children. The intervention was based on both Projeto Parceria manuals. Instruments of data collection involved: Inverview With Women Victims of Domestic Violence, at the first session; the instruments Beck Depression Inventory (BDI); Child Abuse Potential Inventory (CAP) and Parenting Styles Inventory (Inventário de Estilos Parentais) applied at the pre-test, post-test and follow up phases; a Daily-Record of Wellbeing and Parental Competence Sense, collected weekly, and and Evaluation by the participants, at the last session. The project was approved by the University s Research Ethics Committee, and the initial screening of participants took place. The Interview was conducted to compose three groups evenly, each comprising one type of procedure. Subsequently, data collection and intervention took place, in which the sessions were conducted individually. The study was conducted at the University and lasted 20 sessions. It was utilized a non-randomized clinical trial with intra-group comparisons over time as Research Design. The data from inventories were analyzed by the JT Method, which evaluates the Clinical Significance and Reliable Positive Changes of instruments scores. Furthermore, data from Daily Records were analyzed using frequency charts and the Evaluation of Participants by Content Analysis. Results showed more positive indicators throughout the groups scores, when compared pre-test, post-test and follow up phases, and the group which comprised Unit 1 and Unit 2 simultaneously showed best results. All participants evaluated the Project in a positive way. The present study has achieved its objective, which was to compare the efficacy of three different types of intervention procedures to mothers with history of domestic violence, and it has indicated the one which mixes both procedures simultaneously as the most effective. Participants adhesion to the program was excellent (100%), which is rarely found in women with such profile. Limitations were found in the study that could be involved controlling the variable severity of violence experienced by participants, as well as the inclusion of other informants in data collection measures. In conclusion, it is suggested that Projeto Parceria incorporates the referred procedure and it should be replicated at other institutions that support women who are victims of violence to maximize its adoption as Public Policy.
Effectiveness of procedures to maximize sense of well-being and parental compentence to victimizes women
Keywords: Psicologia; Violência doméstica; Estilos parentais; Programa de intervenção; Prevenção de problemas de comportamento; Terapia cognitivo-comportamental; Avaliação de intervenção com mães; Domestic violence; Parenting styles; Assessment of intervention with mothers; CIENCIAS HUMANAS::PSICOLOGIA